Forced Labour of Polish and Soviet Children Under Nazi Occupation Discussion by Prof. Johannes-Dieter Steinert and Prof. Beata Halicka, 1 December 2022 - Halicka, Beata; Steinert , Johannes-Dieter (Studia Historiae Oeconomicae, 2023)
The following conversation is an abridged transcript of a discussion that Prof. Dr. Beata Halicka (UAM) held with Prof. Dr. Johannes-Dieter Steinert of the University of Wolverhampton in the UK. It took place on December 1, 2022 and was the opening event of a conference entitled Little Workers: Child Labor in socio-cultural and economic perspectives throughout history. The conference was organized by the Department of Economic History, the Department of Eastern European History and the Research Unit of Cultural History and was held at the Faculty of History of Adam Mickiewicz University in Poznan. Johannes-Dieter Steinert is a prominent specialist in the field of child forced laborers in National Socialist Germany and German occupied Eastern Europe. His books on the subject have been published in English, German and Polish.